2020
DOI: 10.1002/anie.202001439
|View full text |Cite
|
Sign up to set email alerts
|

Bis(imino)carbazolate: A Master Key for Barium Chemistry

Abstract: Reported here is ar eadily available bis-(imino)carbazole-based proligand that constitutes aconvenient entry point into the challenging synthetic molecular chemistry of barium. It enables the preparation of rare or even, up to now, unknown, solution-stable heteroleptic barium complexes.T he syntheses and structural features for the first molecular barium fluoride and the first barium stannylide,w ith an unsupported BaÀSn bond, are described, along with other carbazolate barium species:a na mide (both ar emarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Syntheses of the heteroleptic complexes [{BDI DiPeP }BaN(SiMe 3 ) 2 · (thf) x ] (x = 0 or 1), [{DPM Anth }BaN(SiMe 3 ) 2 ], [{CH(Ph 2 P=N‐SiMe 3 ) 2 }Ba(µ‐I) · (thf) 2 ] 2 [98b] and complexes supported by the bis(imino)carbozate {Carb DiPP } – …”
Section: Heteroleptic Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of the heteroleptic complexes [{BDI DiPeP }BaN(SiMe 3 ) 2 · (thf) x ] (x = 0 or 1), [{DPM Anth }BaN(SiMe 3 ) 2 ], [{CH(Ph 2 P=N‐SiMe 3 ) 2 }Ba(µ‐I) · (thf) 2 ] 2 [98b] and complexes supported by the bis(imino)carbozate {Carb DiPP } – …”
Section: Heteroleptic Complexesmentioning
confidence: 99%
“…It has recently been reported that a bis(imino)carbazolate ligand {Carb DiPP } – has been used to stabilize a broad range of heteroleptic barium species including the first fluoride, silanide and stannylide species . The four‐coordinate heteroleptic barium amide [{Carb DiPP }BaN(SiMe 3 ) 2 ] was synthesized in 92 % yield from the protonolysis between {Carb DiPP }H and [Ba{µ‐N(SiMe 3 ) 2 }{N(SiMe 3 ) 2 }] 2 .…”
Section: Heteroleptic Complexesmentioning
confidence: 99%
“…Stopping these phenomena, which are most troublesome for the largest and most electropositive element barium, still constitutes a challenge in modern alkaline‐earth molecular chemistry. Yet, thanks to the use of carefully devised ligands, for example β‐diketiminates, [12,32] iminoanilides, [12] carbazolates, [33–34] phenoxides, [6,35–36] or tris(pyrazolyl)borates, [37] the number of stable, heteroleptic barium complexes has been growing steadily in recent years. Beyond homogenous catalysis, these ligands have led to breakthroughs such as the recent preparation of soluble barium‐hydrides [31,37–38] …”
Section: Introductionmentioning
confidence: 99%
“…Compound 5 was readily prepared by the oxidative-addition of hexamethyldistannane to calcium metal, 43 the synthesis of 6 and 7 utilised salt metathesis routes from group 1-metallated precursors. [44][45][46] Neither of these strategies, however, is likely to be amenable to incorporation into catalytic cycles. Since the formation of 3 and 4 is redox neutral at calcium and generates H 2 instead of insoluble salts as a by-product, therefore, it holds attractive potential for the development of Ae-based catalysts for processes such as hydrostannylation or stannane dehydrocoupling.…”
Section: Introductionmentioning
confidence: 99%